A labeled sequent calculus for propositional linear time logic - Alonderis, Romas (Lietuvos matematikos rinkinys, 2012)
A labeled sequent calculus LSC for propositional linear discrete time logic PLTL is introduced. Its sub-calculus LSC−TL is proved to be complete for some class of PLTL sequents.
Keywords: labeled sequent calculus; temporal logic